Nghiên cứu hoá học và hoạt tính sinh học cây diếp cá suối Gymnotheca chinensis Decne (Saururaceae). Phần 1. - Hương và cộng sự, Hoàng Thanh (Vietnam Journal of Chemistry, 2014)
Phytochemical investigation on Gymnotheca chinensis Decne growing in Vietnam led to the isolation of three pentacyclic tritecpenoids. On the basis of spectroscopic data, the structures of these compounds were established as 3b-hydroxy-olean-12-en (b-amyrin, I), 3b-hydroxy-urs-12-en-28-oic acid (ursolic acid, II) and 3b-acetoxy-urs-12-en-28-oic acid, (3b-acetoxy ursolic acid, III).